Pengembangan Media Pembelajaran Ansambel Musik Berbasis Video Animasi Untuk Kelas VII SMP Negeri 25 Padang - Sri Sundari; Erfan Erfan (FBS Universitas Negeri Padang, 2022)
This research aims to find out how the process of developing music ensemble learning media based on animated videos and the validity of the development of animation video-based music ensemble learning media for class VII of SMP Negeri 25 Padang.This type of research is Research and Development (R&D), using ADDIE development models, namely Analysis, Design, Development, Implementation, and Evaluation. This research instrument is in the form of product validation sheets and student response questionnaires. Data collection techniques are carried out by means of library studies, observations, interviews and documentation. The data analysis techniques in this study are validation sheet analysis and student response questionnaire analysis.The result of this research is the development of educational media music ensembles based on animated videos carried out by passing the main stages, where there are five stages carried out, namely 1) Analysis of the needs of learners, 2) Design of learning media, 3) Development or media development, 4) Implementation or trial of products, and 5) Product evaluation. At the development stage, after the product is developed first the product is validated and then revised according to the advice before finally being tested. Validation results conducted by three validators after analysis produce the following data: (1) media expert validation sheets obtain an average of 4.2 with a percentage of 84% and the media category is very valid / decent, (2) the material expert validation sheet obtains an average of 4 and reaches an 80% percentage with a very valid / decent media category,(3) Validation sheets by educators earn an average of 4.1 reaching a percentage of 82% with a very valid / decent media category. The response of learners to the development of the learning media of music ensembles based on animated videos is satisfactory with good categories.